Prevalence of precancerous lesions and conditions in Telangana region, Andhra Pradesh, India - B Hari Vinay; P Venkat Baghirath; J Vijay Kumar; Arvind (Wolters Kluwer Medknow Publications, 2014)
Aim: To assess the prevalence of oral precancerous lesions and conditions and to determine the potential risk factors associated among general population aged 20-70 years of Telangana region, Andhra Pradesh. Materials and Methods: An oral screening campaign was organized with the help of local general dental practitioners in each district. All the relevant information regarding the subject was documented and clinical examination of the oral soft tissues was carried out. Clinically diagnosed as precancerous lesion or condition were subjected to punch (incisional biopsy) biopsy and evaluated histopathologically to confirm the diagnosis. Results: Among 1200 screened, 150 subjects were chewers and 136 subjects were smokers with 29 chewers and 16 smokers had precancerous lesions and conditions. An overall prevalence of oral precancerous lesions and conditions were found to be 4.2% (males 5.5%; females 2.5%). Leukoplakia was seen in 0.8%, Oral submucous fibrosis in 1.3% and lichen planus in 2% of the study population. Conclusions: The prevalence of precancerous lesions and conditions in our study is higher when compared with the reports from different parts of the country and in South East Asia. These lesions can be prevented from malignant transformation by mass screening, close monitoring, early detection, appropriate treatment plan and prognosis.